(untitled) (Research, Society and Development, 2021)
Obesity is a nutritional disorder caused by the excessive accumulation of white adipose tissue (WAT) in the body, which is characterized by a high body mass index and interferes with the body’s energy balance. Obesity is a major risk factor for a number of different diseases, such as type 2 diabetes, cardiovascular disease, hypertension, fatty liver disease and some malignant tumors. The treatment of obesity primarily focuses on diet and physical exercise; when lifestyle changes fail, drugs and surgery will be considered as treatment options. At present, a number of so‑called anti‑obesity drugs have been developed, which affect digestion and absorption. These drugs can produce significant weight loss in the individual; however, some patients are unwilling to receive this type of treatment, due to side effects such as insomnia, hypertension and dizziness. This perspective shows that rational design is an alternative methodology based on native bioactive molecules for the development of analogous compounds, improved from the point of view of efficiency and side effects. We also show that the modification of peptides from animal toxins can be an interesting alternative in the treatment of obesity, since peptides from toxins have already shown significant anti-inflammatory effects.